X-Ray Reflectivity Analysis of Titanium Dioxide Thin Films Grown by Cathodic Arc Deposition - Kleiman, Ariel Javier (2014)
TiO2 thin films deposited by a vacuum arc on a glass substrate were characterized by X-ray reflectivity (XRR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy (AFM). Several thin films with different amounts of deposited TiO2 mass and different deposition and annealing temperatures were studied. A qualitative analysis of the XRD patterns indicated the presence of the anatase and/or rutile crystalline phases in most of the studied samples. From the analysis of the experimental XRR curves—which exhibited a wide angular range of oscillatory behavior—the thickness, mass density and interface roughness were determined. All XRR patterns were well fitted by modeled curves that assume the presence of a single and homogeneous TiO2 layer over which a very thin H2O layer is adsorbed. The thickest H2O adsorption layers were developed in films with the highest anatase content. Our overall results of the XRR analyses are consistent with those derived from the imaging techniques (SEM and AFM).